Effects of communication training with the MAAS-Global-D instrument on the antibiotic prescribing for respiratory infections in primary care: study protocol of a randomised controlled trial. Issue 1 (December 2016) - Hammersen, Friederike; Goetz, Katja; Soennichsen, Andreas; Emcke, Timo; Steinhaeuser, Jost
Abstract Background Primary care physicians account for the majority of antibiotic prescribing in ambulatory care in Germany. Respiratory diseases are, regardless of effectiveness, often treated with antibiotics. Research has found this use without indication to be caused largely by communication problems (e.g. expectations on the patient's part or false assumptions about them by the physician). The present randomised controlled trial (RCT) study evaluates whether communication training for primary care physicians can reduce the antibiotic prescribing rate for respiratory tract infections. Methods/Design The study consists of three groups: group A will receive communication training; group B will be given the same, plus additional, access to an evidence-based point-of-care tool; and group C will function as the control group. The primary endpoint is the difference between intervention and control groups regarding the antibiotic prescribing rate before and after the intervention assessed through routine data. The communication skills are captured with the help of the communication instrument MAAS-Global-D, as well as individual videos of physician-patient consultations recorded by the primary care physicians. These skills will also be regarded with respect to the antibiotic prescribing rate. A process evaluation using qualitative as well as quantitative methods should provide information about barriers and enablers to implementing the communication training. Discussion The trial contributes to an insight into the effectiveness of the different components to reduce antibiotic prescribing, which will also be supported by an extensive evaluation. Communication training could be an effective method of reducing antibiotic prescribing in primary care. Trial registration DRKS00009566 Date registration 5 November 2015.